Jesus’ Breath: A Physiological Analysis of pneu͂ma within Paul’s Letter to the Galatians - Barrier, Jeremy W. (Journal for the study of the New Testament, 2014)
In Gal. 3.14-16 Paul connects the ‘promised’ σπέρμα of Abraham with the experience of the ‘spirit’ in Galatia. Since ‘spirit’ occurs nowhere in Gen. 12–22, Paul’s equation (i.e., ‘promise’ equals ‘spirit’) is considered to be an interpretive leap. This article is an attempt to explain this gap by demonstrating how Paul’s argument hinges upon a Greco-Roman physiological metaphor. By ﬁrst outlining ancient concepts of physiology, and in particular the role of πνεῦμα as it relates to the σπέρμα of the human body, one can see how these ideas would have been understandable even within the popular imagination. The role of πνεῦμα within Gal. 3 makes better sense when it is understood according to ancient notions of physiology and medicine. Recognition of the physiological language employed by the apostle in Galatians leads to an enhanced understanding of Pauline theology.